INOKUL ASI FUSARIUM sp. PADA POHON KARAS (Aquilaria malaccencis Lamk.) TERHADAP PEMBENTUKAN GAHARU - Azwin, Azwin (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
This study aimed to get a dose of right inoculants Fusarium sp. and accelerate the creation of aloes. This research was conducted in test models of agro forestry plots and aloes-owned Balai Penelitian dan Teknologi Serat Tanaman Hutan (BPTSTH) Kuok that located in the village of Kembang Damai Districts of Pagaran Tapah Darussalam Rokan Hulu District. Held for 3 months from July to September 2013. The research method using a randomized block design with 5 treatments, namely in drill without being given inoculant fungi Fusarium sp. (Control), (P1), inoculant 0.5 cc / hole (P2), inoculant 1 cc / hole (P3), inoculant 1.5 cc / hole (P4), inoculant 2 cc / hole (P5). Each treatment was appli.ed in three (3) blocks, the first block to the treatment of Karas trees to plant oil palm on a spacing of 2 meters, block II spacing of 3 meters and a block III at spacing of 4 meters. After 3 months of observation of the extensive infection, discoloration and changes in the level of flavor very significant effect. A symptom o f the infection area formed on the aloe tree tends to spread vertically to follow the direction of the vascular tissue of the stem. To aloes Â± 6 years old should use a dose of 0.5 cc / borehole inoculant Fusarium sp.